Dynamics Capital Structure of Firms in Indonesia Stock Exchange - Arni Surwanti (Tamkang University, 2012)
this study attempted to examine the dynamic capital structurew model based on a sample on manufacturing company in Indonesia. the data used is panel data of listed companies in Indonesia Stock exchange in the period 2000-2008